Mining dams disasters as systemic risks - Carlos Machado de Freitas; Mariano Andrade da Silva; Fernanda Carvalho de Menezes; Zélia Maria Profeta da Luz (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Between 2015 and 2019, Brazil recorded the two most serious disasters involving mining dams of the 21st century. The purpose of this article is to offer an understanding of these disasters as systemic risks. They involve from global and national processes related to social determinants that materialize in a complex system of dams distributed throughout the country with their intrinsic risks. When they occur, result in a set of impacts with potential damage and immediate effects combined with secondary and tertiary impacts that can trigger chain reactions, which promote risk factors of heterogeneous and complex occurrence. Approaching these events from the point of view of systemic risk allows for a broader understanding of both the singularity of each of these disasters and their multiple exposure, risk and disease processes, as well as the structural characteristics in which social, political processes and dynamics and economic factors reproduce in multiple territories a common pattern of disasters and their effects. We conclude that the promotion of population health and sustainable territories should guide the organization of production processes and not the opposite, with the externalization of human, environmental and social costs of mining and its disasters.